Dakwah Pendekatan Kultural - Hermawati Hermawati; Zulkhairit Zulkhairit (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2013)
Da'wah is an invitation for the good of the teachings of Islam, commanding the good and forbidding the evil. Da'wah cultural approach is the approach implemented by making culture as a means of propaganda. Utilization of cultural aspects in society aims to achieve the goal of preaching. Relevanced propaganda material culture in the society so that the process of delivering propaganda materials performing well. Media in the process is the primary means of propaganda potential to move the information to the public in accordance cultures that exist in society and methods used in the process of propaganda must be adapted to the culture that exists in society.